THE SOCIAL NECESSITY OF LANGUAGE CONTACT AND THE STUDY OF SCIENCE (For example, Uzbek and Kazakh languages) - Abduvalitov Yergash Buranevich,; Abduvalitov Nurjan Buranevich,; Sayfullayev Baurjan Nurumbetovich, (The Bioscan, 2025)
In world linguistics, attention has increased to the issue of language contact. As is known, the development features of historically connected languages and dialects and the increase in population migrations in the world are opening a wide path to language contact. This problem has occurred at all stages of human society, but its scientific study was associated with the emergence of comparative-historical linguistics in the world in the 19th century. The “wave theory”1 that emerged during this period proved the naturalness of the contact between languages. Language contact has been called differently in world linguistics. Among them, the concept of “language union” is popular, which continued in subsequent periods. Although the concept of “language contact” does not completely replace the concept of “language union”, it can combine their common features. This raises an urgent issue for every linguistics, including Turkology, which is the basis of our research work. In world linguistics, several types of language contact are noted: language contact, bilingualism, word acquisition, interference, substrate, etc. Taking them into account in this work, it is relevant to study the issue of the reflection of the features inherent in the Uzbek language in the Kazakh literary literature created in the conditions of bilingualism in the area of these peoples as a result of a new process, namely, the contact of the languages of the Uzbek and Kazakh peoples, who historically lived in the same space1. Also, theoretical research is being developed in the science of texts that are the result of research on language contact in terms of lexical-semantic, syntactic-semantic, functional-stylistic, communicative-pragmatic and other aspects. Now, along with the theoretical study of the features of language contact, there are also works devoted to its new direction, which we are promoting, namely, the influence of the leading language in the dialectal zone on the language in contact and their use in the work of writers who have grown up in this area1, but the issue of the use of the Uzbek language and its dialect-specific features in the works of writers who have grown up in the Republic of Uzbekistan and were formed in the spirit of Uzbek dialects has not been the object of research so far. This problem is the current issue of our research work.